2018
DOI: 10.1177/1120672117752423
|View full text |Cite
|
Sign up to set email alerts
|

Pars plana vitrectomy with silicone oil tamponade for primary and secondary macular hole closure: Is it still a useful procedure?

Abstract: There are reports on good efficacy of silicone oil tamponade for primary and recurrent macular hole closure. Anatomical closure and visual acuity rates in pars plana vitrectomy with silicone oil and with gas filling are comparable. Gas tamponade seems to be safer and needs no more surgery. Postoperative complications in both methods are similar, but all patients with silicone oil filling need to undergo a reoperation to have the silicone removed. There are also other surgical techniques for primary macular hol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…However, the operation procedure is complicated which may increase the risk of infection. Rao X reported that 89% patients achieved anatomic success after the outpatient inflating gas-fluid exchange by two needles for open macular hole after primary vitrectomy [ 15 , 16 ]. Additional intravitreal inflating gas injection can achieve complete macular hole closure for unsealed macular hole ≤700 µm [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the operation procedure is complicated which may increase the risk of infection. Rao X reported that 89% patients achieved anatomic success after the outpatient inflating gas-fluid exchange by two needles for open macular hole after primary vitrectomy [ 15 , 16 ]. Additional intravitreal inflating gas injection can achieve complete macular hole closure for unsealed macular hole ≤700 µm [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is unknown whether a further ILM peeling extension passed the vascular arcades alone, or in conjunction with A-ILM techniques, may give any adjunctive benefit. It should also be noticed that many re-operation techniques including further bubbling, 10 silicone oil tamponade, 11 ILM peeling enlargement, macular detachment 13 and full-thickness retinal transplantation 14 have been proposed, while we only compared A-ILM versus what we routinely used: ILM peeling enlargement and further tamponade. Pitfalls of this study should also mention the relatively short follow-up and limited series dimension.…”
Section: Discussionmentioning
confidence: 99%
“…Proposed treatment options for recurrent idiopathic macular holes (r-IMHs) vary greatly from the simple introduction of a novel gas bubble 10 to silicone oil tamponade, 11 ILM peeling enlargement, use of ILM flaps, autologous internal limiting membrane (ILM) transplantation, 12 induction of macular detachment 13 and autologous full-thickness retinal transplantation. 14…”
Section: Introductionmentioning
confidence: 99%
“…Known adverse effects include inflammation [35] and silicone emulsification [33,35], elevated IOP [33] and potential development of secondary glaucoma [35] and accelerated nuclear sclerosis [36] with cataract formation [33]. Pieczynski et al meta-analysis on the current silicone oil tamponade found good efficacy for primary and recurrent MH closure, with the method being similar for complications with gas tamponade [38], however requiring the second silicone extraction surgery [39] and indicated it as an alternative after gas tamponade [39]. Functional outcomes after MH closure surgery are dependent on the restoration of the foveal structure, particularly regarding the outer retinal segment [46].…”
Section: Figure 3 -Comparison Of Pre-op Va and Va At One-year Post-op...mentioning
confidence: 99%